2022
DOI: 10.3748/wjg.v28.i21.2334
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin type 3 receptor subunit gene polymorphisms associated with psychosomatic symptoms in irritable bowel syndrome: A multicenter retrospective study

Abstract: BACKGROUND Single-nucleotide polymorphisms (SNPs) of the serotonin type 3 receptor subunit ( HTR3 ) genes have been associated with psychosomatic symptoms, but it is not clear whether these associations exist in irritable bowel syndrome (IBS). AIM To assess the association of HTR3 polymorphisms with depressive, anxiety, and somatization symptoms in individuals with IBS. METHODS In this ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In particular, the signal trasduction mechanism of 5-HT3 receptor is a ligand-gated ion channel (Na + /K + ), the binding of serotonin resulting in plasma membrane depolarization, whereas other 5-HT receptors are G protein-coupled receptors (GPCRs) and activated by cAMP. And 5-HT3 receptor had been proved to be positively expressed in lung cancer and colorectal carcinoma 19 , 20 . Schneider et al discovered that administration of antidepressants serotonin reuptake inhibitors (SSRIs) promoted the action of PD-1 checkpoint blockers and inhibited the tumor growth of untreatable pancreatic and colorectal cancers 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the signal trasduction mechanism of 5-HT3 receptor is a ligand-gated ion channel (Na + /K + ), the binding of serotonin resulting in plasma membrane depolarization, whereas other 5-HT receptors are G protein-coupled receptors (GPCRs) and activated by cAMP. And 5-HT3 receptor had been proved to be positively expressed in lung cancer and colorectal carcinoma 19 , 20 . Schneider et al discovered that administration of antidepressants serotonin reuptake inhibitors (SSRIs) promoted the action of PD-1 checkpoint blockers and inhibited the tumor growth of untreatable pancreatic and colorectal cancers 21 .…”
Section: Discussionmentioning
confidence: 99%
“…TPH2 has its most significant impact in the serotonin pathway. The study of somatization in other conditions often also points to serotonin [ 30 , 31 , 32 ]. A study showed increased methylation of the oxytocin receptor gene in 15 patients with motor functional neurological disorder compared with healthy controls [ 33 ].…”
Section: Discussionmentioning
confidence: 99%